Low hysteresis in composites ceramics achieved by building polarization field and restoring force - Fangfang Zeng; Zhaokai Yao; Qiansi Zhang; Peng Peng; Xi Feng; Rongchuan He; Rongshan Zhou; Huitao Guo; Quan Xie; Guifen Fan; Qingquan Xiao; Li Zhang; et al. (Materials & Design)
Large strain hysteresis and remnant strain are one of the vital reasons for the absence of BiFeO3-BaTiO3-based ceramics in commercial actuator fields. Here, we elaborately propose a strategy, preparing 0–3 type composite ceramics, to reduce the hysteresis and remnant strain, and the target is successfully achieved by building restoring force and polarization field. Normal strain constant and electric field-induced strain in 0–3 composites have enhanced by 260% and 196% compared to those of non-composite ceramics, respectively. Also, hysteresis and remnant strain in 0–3 composites have decreased by 35.9% and 50.6% in contrast to those of non-composites. Superior electrostrain properties under the low electric field are attributed to the construction of polarization field, restoring force, and micro-capacitance, coinciding with phase field simulation, and the strategy will pave a useful way to optimize the hysteresis and remnant strain in BiFeO3-BaTiO3-based high-temperature ceramics.